Metal–Ligand Cooperation in Dihydrogen Activation by a Cationic Metallogermylene: Enhanced Activity from Tungsten to Molybdenum - Rikiya Matsumoto; Koichi Nagata; Ryo Nakamura; Takahito Watanabe; Hisako Hashimoto (Molecules)
Dihydrogen activation by metallogermylenes was investigated experimentally and theoretically. A neutral NHC-coordinated chlorometallogermylene was synthesized and converted to a cationic base-free metallogermylene of molybdenum via chloride abstraction. The cationic molybdogermylene showed enhanced reactivity toward H2 compared to the tungsten analog. The reaction mechanism was investigated by theoretical calculations, which revealed a novel route that proceeds via a new type of metal–ligand cooperative activation between the metal and divalent germanium moiety. The activation energy of this route is much lower than that of the alternative route via an “oxidative addition” type of reaction on the single Ge(II) center, which is generally proposed for organotetrylenes. The features of the frontier orbitals and the origin of the metal effect on the H2 activation are also described.